Improving the sound absorption behaviour of porous concrete using embedded resonant structures. (March 2021) - Pereira, M.; Carbajo, J.; Godinho, L.; Ramis, J.; Amado-Mendes, P.
Abstract: A relatively new concept of sound absorption herein denominated as Metaporous concrete is presented, consisting of a porous concrete-based sound absorber in which different acoustic resonators are embedded. Two finite element models were implemented, using the fluid-equivalent theory to describe Metaporous concrete solutions. A Helmholtz resonator, porous concrete samples, and a Metaporous concrete prototype were built and tested through experimental techniques based on the use of an impedance tube. The fluid-equivalent complex properties were validated with comparisons between analytical predictions and experimental data. The proposed numerical tools were presented as an efficient methodology to predict the sound absorption behavior of Metaporous concrete solutions, where an excellent approach between the simulated results and experimental data is shown. The parametric study shows efficient strategies to increase the sound absorption behavior and to feature the two sound absorption coefficient peaks provided by Metaporous concrete solutions (i. e. from the acoustic resonator and the porous concrete, respectively). The denominated configuration MPCd was highlighted because of the great proximity of these two sound absorption peaks. The inclusion of non-trivial resonant structures in porous concrete, building a Metaporous concrete, can be proposed as an excellent solution to be adopted for noise control in civil engineering exterior applications. Higlights: Analysis of a porous concrete-based sound absorber in which different acoustic resonators are embedded. Fluid-equivalent theory in finite element models used to describe sound absorption behavior of metaporous concrete solutions. The increase of sound absorption range and sound absorption coefficient peaks of metaporous concrete analyzed. The use of resonant structures embedded in porous concrete proposed for noise control in engineering exterior applications.